1992
DOI: 10.1042/bj2820273
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of extracellular-matrix proteins by human cathepsin B from normal and tumour tissues

Abstract: Our laboratory has previously demonstrated that increased malignancy of several histological types of human and animal tumours is associated with increases in their cathepsin B activity, particularly cathepsin B activity associated with plasma-membrane/endosomal vesicles or shed vesicles. Here we report that cathepsin B from normal or tumour tissues degrades purified extracellular-matrix components, type IV collagen, laminin and fibronectin, at both acid pH and neutral pH. The number and sizes of degradation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
213
0
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(226 citation statements)
references
References 33 publications
2
213
0
5
Order By: Relevance
“…This is consistent with a recent study demonstrating that independent CtsB and CtsX deficiencies in mice have only marginal effects on breast cancer development and metastasis, while their combined deficiencies result in considerable reduction of metastatic potential [48]. The involvement of CtsB in direct degradation of ECM proteins, including collagens I and IV, fibronectin, and laminin, promoting the invasion of various human cancers, is well documented [49]. Thus, the participation of CtsB in ECM degradation of human Mfs is not unexpected.…”
supporting
confidence: 78%
“…This is consistent with a recent study demonstrating that independent CtsB and CtsX deficiencies in mice have only marginal effects on breast cancer development and metastasis, while their combined deficiencies result in considerable reduction of metastatic potential [48]. The involvement of CtsB in direct degradation of ECM proteins, including collagens I and IV, fibronectin, and laminin, promoting the invasion of various human cancers, is well documented [49]. Thus, the participation of CtsB in ECM degradation of human Mfs is not unexpected.…”
supporting
confidence: 78%
“…Cystatin M (CST6) functions as an endogenous inhibitor of lysosomal cysteine proteases (Ni et al, 1997;Sotiropoulou et al, 1997), which are known to contribute to tumor cell invasion by degrading extracellular matrix components (Buck et al, 1992;Maciewicz et al, 1990;Mai et al, 2002). Cathepsin B and cathepsin L are two important cysteine proteases that have been implicated in tumor cell invasion and metastasis (Kane and Gottesman, 1990;Roshy et al, 2003;Slone et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…However, it also seems possible that MARCKS may regulate in some way the action or secretion of cathepsin B. For example, it is known that cathepsin B can degrade laminin, fibronectin, and collagen (75)(76)(77) and can activate the urokinase-type plasminogen activator associated with tumor invasiveness (78). Studies from our laboratory have shown that the brains of mice completely lacking MARCKS exhibit deficiencies in at least two types of extracellular matrix molecules, laminin and chondroitin sulfate proteoglycans (79).…”
Section: Figmentioning
confidence: 99%